Reconsidering the Active Psychological Ingredients Underlying Intercultural Adaptation: Implications for International Business - Matsumoto, David; Hwang, Hyisung C. (Frontiers in Psychology, 2020)
A major issue facing many businesses today, both large and small, concerns intercultural adaptation, and more broadly, diversity. Many businesses struggle with their employees sent to different countries and cultures to adapt effectively in host cultures, as well as for their home culture employees to adapt effectively to changing environments brought on by visitors from other cultures and other sources of diversity. To address this issue, many tests and measures have been developed to identify the core psychological skills, competencies, and aptitudes underlying intercultural adaptation. Elucidation of such skills and competencies would have multiple theoretical and practical ramifications. A recent review of this literature indicated that three tests – the Multicultural Personality Questionnaire, the Cultural Intelligence Scale, and the Intercultural Adjustment Potential Scale – had the best psychometric evidence for validity to date. No study, however, has examined the statistical overlap among these tests; which scales or combination of scales best predict adaptation; and most importantly, what are the possible, yet unassessed, constructs underlying them. The purpose of this study was to examine these three questions initially. Non-immigrant, non-sojourner convenience samples from four countries/language groups completed all three tests and a measure of life satisfaction as a proxy for adaptation. Scales from the three tests were moderately – highly intercorrelated and predicted adaptation. A combination of scales from the tests best predicted adaptation, better than scales from any one test. Analyses examining the latent structures underlying the combined tests suggested several psychological constructs new to the intercultural adaptation literature. We discuss the implications of these findings for theory and application in international business.